Carbon-coated graphite negative electrode material with gradient pores and preparation method of carbon-coated graphite negative electrode material

By forming a gradient porous carbon coating layer on the outside of graphite material, the lithium-ion diffusion path and electrode structure stability are optimized, solving the polarization and peeling problems of graphite anode materials during high-rate charge and discharge, and achieving higher rate performance and longer cycle life.

CN120854508APending Publication Date: 2025-10-28HUNAN CHMM-SUNWARDS NEW MATERIAL CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202510768012.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-06-10
Publication Date
2025-10-28

AI Technical Summary

Technical Problem

Existing graphite anode materials have long lithium-ion diffusion paths during high-rate charge and discharge, resulting in significant polarization during charge and discharge and a risk of lithium plating. Traditional coatings are prone to peeling off after repeated charge and discharge, making it difficult to achieve high-rate and long-cycle performance.

Method used

Gradient porous carbon-coated graphite material is used. By forming first and second carbonized graphite coating layers on the outside of the graphite core, the carbon pore size and porosity are controlled. Stepwise impregnation and high-temperature carbonization are used to form a gradient porous structure with a dense inner core and a loose outer core, thereby optimizing the ion transport path and structural stability.

Benefits of technology

It improves the lithium-ion diffusion rate, reduces lithium dendrite formation, enhances electrode structure stability, and improves the rate performance and cycle life of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention relates to the technical field of graphite materials, in particular to a carbon-coated graphite negative electrode material with gradient pores and a preparation method of the carbon-coated graphite negative electrode material. The method comprises the following steps: performing crystal high-temperature carbonization on the surface of graphite powder by adopting a carbon skeleton precursor to form a carbon skeleton layer, constructing a dipping carbon source solution in the carbon skeleton layer in a step-by-step dipping manner to form gradient distribution, and performing high-temperature carbonization at 1000-1400 DEG C to obtain the carbon-coated graphite material with gradient pores. The design of the gradient pore structure optimizes the ion transmission path, reduces the interfacial effect, and avoids lithium dendrites formed by Li < + > which cannot be diffused and gathered on the surface of the graphite negative electrode in time during large-current charging of a traditional structure, so that the rate capability of the graphite negative electrode is improved; the coating layer is effectively prevented from falling off from graphite in the charging and discharging process, and the stability of the electrode can be further improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of graphite materials technology, and in particular to a graphite anode material with gradient pore carbon coating and its preparation method. Background Technology

[0002] As the demands for charging speed from new energy vehicles continue to increase, fast charging has become one of the key technologies for solving "charging anxiety." Graphite anode fast charging technology is developing towards higher charging rates, longer cycle life, and greater safety and reliability to meet the needs of new energy vehicles for fast charging and long driving range.

[0003] The layered structure of graphite determines the properties of Li + It can only be embedded from the end face of the material and gradually diffuse into the interior of the particles, causing Li + The long diffusion path and its small interlayer spacing also limit the diffusion of Li. + Due to the movement of the material, its fast charging performance is poor, and it exhibits significant polarization during charging and discharging at high rates, with a risk of lithium plating.

[0004] Currently, there are two main strategies to improve the fast charging performance of graphite: One approach is to alter the structural characteristics of graphite, such as reducing particle size, increasing interlayer spacing, creating pores, doping, or introducing defects, thereby shortening the lithium-ion diffusion path and accelerating lithium-ion diffusion efficiency. However, this usually damages the graphite structure, increases the specific surface area, and leads to instability in the cycling process and reversible capacity loss.

[0005] Secondly, surface coating of graphite can be applied, such as with carbon materials, metal oxides, and polymers. However, traditional coatings are generally homogeneous, resulting in a single pore size that leads to a relatively high Li+ diffusion activation energy. During high-rate fast charging, lithium dendrites form at the edges, and the interface between the coating layer and graphite is prone to shear stress after repeated charging and discharging, causing the coating layer to peel off. This makes it difficult to achieve breakthroughs in higher rates and cycle performance. Summary of the Invention

[0006] The main objective of this invention is to provide a graphite anode material with gradient porosity carbon-coated graphite and its preparation method, so as to solve the above-mentioned technical problems.

[0007] To achieve the above objectives, the present invention provides a graphite material with gradient porosity carbon coating, comprising a graphite core and a first carbonized graphite coating layer and a second carbonized graphite coating layer sequentially coating the outside of the graphite core; wherein, the carbon pore size of the first carbonized graphite coating layer is smaller than the carbon pore size of the second carbonized graphite coating layer, the porosity of the first carbonized graphite coating layer is 8%~12%, and the porosity of the second carbonized graphite coating layer is 25~40%.

[0008] Preferably, the graphite core includes graphite powder and a carbon skeleton layer formed by high-temperature carbonization covering the graphite powder, wherein the carbon skeleton is artificial graphite.

[0009] Preferably, the thickness of the carbon skeleton layer is 50-200 nm; the total thickness of the first carbonized graphite coating layer and the second carbonized graphite coating layer is 50-200 nm.

[0010] This invention also provides a method for preparing a carbon-coated graphite material with gradient porosity, comprising the following steps: S1, Disperse organic carbon sources with a residual carbon value ≥50% in a solvent to form carbon source solution A; S2, dispersing graphite powder in carbon source solution A to form a slurry; S3, the above slurry is spray-dried to remove the solvent and obtain intermediate powder; S4, the intermediate powder is carbonized at a high temperature of 800-1200℃ to obtain a graphite core with a carbon skeleton layer coating graphite powder. S5, the graphite core is immersed in carbon source solution B1 for T1 time, centrifuged and dried, and then subjected to low-temperature carbonization at 200-500℃ to obtain intermediate material C1; S6, the intermediate material C1 is immersed in a carbon source solution B2 containing additives for time T2, centrifuged and dried to obtain intermediate material C2; wherein, the carbon source concentration in the carbon source solution B1 is greater than the carbon source concentration in the carbon source solution B2, the time T1 is greater than the time T2, and the additive is one or more selected from polyvinyl alcohol, polystyrene, polymethyl methacrylate, and polyvinyl alcohol. S7, intermediate material C2 is carbonized at high temperature of 1000-1400℃ to obtain carbon-coated graphite material with gradient pores.

[0011] Preferably, the organic carbon source of the carbon source solution A is one or more selected from petroleum asphalt, coal tar pitch, epoxy resin, and phenolic resin; the solvent is one or more selected from toluene, ethyl acetate, acetone, ethanol, and tetrahydrofuran; and the graphite powder is artificial graphite. 50 It is 5-20μm.

[0012] Preferably, the carbon source of carbon source solution B1 is selected from one or more of sucrose, polyacrylonitrile, and citric acid, and the solvent is selected from one or more of water, ethanol, N-methylpyrrolidone, and dimethylamide; the carbon source of carbon source solution B2 is selected from one or more of sucrose, polyacrylonitrile, and citric acid, and the solvent is selected from one or more of water and ethanol.

[0013] Preferably, the carbon source concentration in carbon source solution B1 is 10-25 wt%, the carbon source concentration in carbon source solution B2 is 5-15 wt%, and the concentration of the additive is 1-5 wt%; the time T1 is 30-120 min, and the time T2 is 5-60 min.

[0014] Preferably, in step S7, the intermediate material C2 is heated to 600-900°C at a heating rate of 1-3°C / min under a protective atmosphere, and then heated to 1000-1400°C at a high temperature at a heating rate of 2-5°C / min, which is higher than the aforementioned low temperature range, to obtain a carbon-coated graphite material with gradient pores.

[0015] The present invention also provides a graphite material with gradient porosity carbon-coated graphite, prepared by any of the preparation methods described above.

[0016] The present invention also provides an application of a carbon-coated graphite material with gradient pores as described above in a battery anode material.

[0017] In this invention, a carbon skeleton precursor (an organic carbon source in carbon source solution A) is first carbonized at high temperature on the surface of graphite powder to form a carbon skeleton layer. Then, a stepwise impregnation method is used to construct a gradient distribution in the impregnated carbon source solution.

[0018] The formation of the aforementioned carbon framework layer begins with liquid-phase coating and spray drying to uniformly distribute the carbon framework precursor on the surface of the graphite powder. During subsequent carbonization, non-carbon elements (such as hydrogen and oxygen) are gradually released, forming a carbon framework layer with a certain porosity inside. Too low a porosity hinders the penetration of the impregnation solution; too high a porosity results in low resistance to the penetration of the subsequent carbon source solution, making it difficult to form a gradient pore distribution in the coating layer. Therefore, to control the porosity of the carbon framework layer, a carbon source with a residual carbon value ≥50% is selected. The thickness of the carbon framework layer can preferably be controlled by a combination of liquid-phase coating and spray drying, with the thickness controlled between 50-200 nm. A coating layer that is too thin will not effectively suppress the volume change of graphite particles, limiting the performance improvement; an excessively thick carbon coating layer will occupy a certain volume and mass, relatively reducing the proportion of active material in the graphite anode.

[0019] To avoid excessive carbon source deposition on the surface during a single impregnation, a step-by-step impregnation process is employed, which facilitates the formation of a more uniform and deeper concentration gradient. To ensure the impregnation effect, a carbon source capable of fully penetrating the carbon framework layer is selected. In the first impregnation, a high-concentration impregnation solution is used. Under higher impregnation pressure and a longer impregnation time, the impregnating carbon precursor solution can fully penetrate the carbon framework coating layer. The relatively small pores formed after low-temperature carbonization increase the density of the internal structure and prevent excessive solution penetration during subsequent impregnations. The second impregnation uses a low-concentration impregnation solution. Under lower impregnation pressure and a shorter impregnation time, the impregnated carbon precursor is mainly distributed on the material surface and near the surface. Because the presence of additives hinders the polymerization and carbonization of the carbon precursor to some extent, and because the additives decompose during carbonization, larger pores can be formed on the material surface, resulting in a loose outer layer structure.

[0020] Finally, to prevent structural collapse during firing, the heating rate needs to be controlled before the pore structure is fixed (600-900℃). Then, the temperature can be raised to 900-1200℃ at a faster rate for final carbonization, which further improves the crystallinity and graphitization of carbon, while making the pore structure more stable, ultimately forming a gradient porous carbon coating layer that is dense inside and loose outside.

[0021] The present invention has at least the following beneficial effects: (1) The design of the gradient pore structure optimizes the ion transport path: the external porous layer can accelerate the wetting of the electrolyte and provide a pathway for Li + It provides more diffusion channels, and the inner layer micropores ensure full contact of lithium storage sites, avoiding local concentration polarization, improving electrode reaction uniformity, and avoiding the problems of high-current charging of lithium in traditional structures. + The lithium dendrites that do not have time to diffuse and accumulate on the surface of the graphite anode form, thereby improving its rate performance; (2) The gradient pore structure design reduces the interface effect. The high density of the inner layer ensures the stability of the structure. The porous structure of the outer layer absorbs the stress caused by the cycle and the gas and volume changes generated during the charge and discharge process, reducing the risk of particle breakage and damage to the entire electrode structure, thereby improving the cycle stability of the battery. The gradient pore coating layer is more firmly bonded to the inside of the particles, which can effectively prevent the coating layer from falling off from the graphite during the charge and discharge process, and can further improve the stability of the electrode. Detailed Implementation

[0022] The technical problems solved by the embodiments of the present invention, the technical solutions adopted, and the technical effects achieved are clearly and completely described below with reference to specific embodiments. Obviously, the described embodiments are only a part of the embodiments of this application, and not all of the embodiments. Based on the embodiments in this application, all other equivalent or obvious variations of embodiments obtained by those skilled in the art without creative effort fall within the protection scope of the present invention. The embodiments of the present invention can be embodied in various different ways as defined and covered by the claims.

[0023] It should be noted that many specific details are given in the following description for ease of understanding. However, it is obvious that the present invention may be implemented without these specific details.

[0024] It should be noted that, in the absence of explicit limitations or conflicts, the various embodiments and their technical features in this invention can be combined with each other to form a technical solution.

[0025] Example 1: The method for preparing porous carbon-coated graphite material with a gradient buffer layer provided in Example 1 includes: S1, 15 parts by mass of coal tar pitch with a residual carbon content of 70% are dispersed in 100 parts by mass of tetrahydrofuran to form carbon source solution A; S2, 30 parts by weight of D 50 =7.0μm artificial graphite was added to 100 parts by mass of the above carbon source solution A and stirred for 2 hours to form a slurry; S3, the above slurry is added to a spray dryer and dried to obtain intermediate powder at a drying temperature of 150°C. S4. The intermediate powder is placed in a box-type carbonization furnace and heated to 1000℃ under nitrogen protection and held for 2 hours to obtain a graphite core with carbon skeleton coated graphite powder. S5, 10 parts by mass of sucrose are dispersed in 100 parts by mass of water to form an impregnation carbon source solution B1; the graphite core prepared above is added to the impregnation carbon source solution B1 and impregnated for 45 min at an impregnation pressure of 0.5 MPa; after impregnation, the graphite core is centrifuged, dried, and then carbonized at 250 °C to obtain intermediate material C1. S6, 5 parts by mass of sucrose and 5 parts by mass of polyvinyl alcohol are dispersed in 100 parts by mass of water to form an impregnation carbon source solution B2; the above intermediate material C1 is impregnated in the impregnation carbon source solution B2 for 10 min under a pressure of 0.1 MPa, and then centrifuged and dried to obtain intermediate material C2. S7, the above intermediate material C2 is placed in a box-type carbonization furnace under a protective atmosphere and heated to 750°C at a rate of 1.5°C / min, and then heated to 1200°C at a rate of 3°C / min and held for 2 hours to obtain the final graphite material with gradient pore carbon coating.

[0026] This embodiment 1 provides a carbon-coated graphite material with gradient porosity, the core being D. 50 =7.0μm artificial graphite, gradient porous carbon-coated graphite anode material D 50 =8.5μm, specific surface area is 2.8m² 2 / g, the outer layer of highly porous carbon has a porosity of 34.6%, the inner layer of dense amorphous carbon has a porosity of 9.2%, and the carbon layer thickness is 120nm.

[0027] The graphite material with gradient porosity carbon-coated graphite obtained in Example 1 was tested for electrical performance. The initial discharge specific capacity was 352.0 mAh / g, the initial coulombic efficiency was 93.1%, the capacity retention rate was 95.3% after 600 cycles at 1C current, and the capacity retention rate was 92.6% at 5C / 0.5C.

[0028] Example 2: The method for preparing porous carbon-coated graphite material with a gradient buffer layer provided in Example 2 includes: S1, 10 parts by mass of epoxy resin with a carbon residue of 55 are dispersed in 100 parts by mass of ethyl acetate solvent to form carbon source solution A; S2, 30 parts by weight of D 50 =12.0μm artificial graphite was added to 100 parts by mass of the above carbon source solution A and stirred for 3 hours to form a slurry; S3, the above slurry is added to a spray dryer and dried to obtain intermediate powder at a drying temperature of 180℃; S4. The intermediate powder is placed in a box-type carbonization furnace and heated to 800℃ under nitrogen protection and held for 2 hours to obtain the graphite core of the graphite powder with carbon skeleton coating. S5, 10 parts by mass of polyacrylonitrile are dispersed in 100 parts by mass of N-methylpyrrolidone to form an impregnation carbon source solution B1; the graphite core prepared above is added to the impregnation carbon source solution B1 and impregnated for 60 min at an impregnation pressure of 0.8 MPa; after impregnation, the graphite core is centrifuged, dried, and then carbonized at 450 °C to obtain intermediate material C1. S6, 8 parts by mass of sucrose and 3 parts by mass of polystyrene are dispersed in 100 parts by mass of water to form an impregnation carbon source solution B2; the above intermediate material C1 is impregnated in the impregnation carbon source solution B2 for 5 minutes under a pressure of 0.2 MPa, and then centrifuged and dried to obtain intermediate material C2; S7, the above intermediate material C2 is placed in a box-type carbonization furnace under a protective atmosphere and heated to 600°C at a rate of 1.0°C / min, then heated to 1100°C at a rate of 3.5°C / min and held for 3 hours to obtain the final graphite material with gradient pore carbon coating.

[0029] The graphite material with gradient porosity carbon coating provided in this embodiment 2, the graphite material with gradient porosity carbon coating D 50 =13.2μm, specific surface area is 2.6m² 2 / g, where the kernel is D 50 The artificial graphite has a thickness of 12.0 μm, with an outer layer of highly porous carbon with a porosity of 33.9% and an inner layer of dense amorphous carbon with a porosity of 9.8%, and a carbon layer thickness of 62 nm.

[0030] The gradient porous carbon-coated graphite material obtained in Example 2 was tested for electrical performance. The initial discharge specific capacity was 352.9 mAh / g, the initial coulombic efficiency was 92.8%, the capacity retention rate was 95.0% after 600 cycles at 1C current, and the capacity retention rate was 92.0% at 5C / 0.5C.

[0031] Example 3: The method for preparing porous carbon-coated graphite material with a gradient buffer layer provided in Example 3 includes: S1, 20 parts by mass of phenolic resin with a carbon residue of 65 are dispersed in 100 parts by mass of ethanol solvent to form carbon source solution A; S2, 40 parts by weight of D 50 =15.0μm artificial graphite was added to 100 parts by mass of the above carbon source solution A and stirred for 3 hours to form a slurry; S3, the above slurry is added to a spray dryer and dried to obtain intermediate powder at a drying temperature of 200℃; S4. The intermediate powder is placed in a box-type carbonization furnace and heated to 900℃ under nitrogen protection and held for 1.5h to obtain a graphite core with carbon skeleton coated graphite powder. S5, 20 parts by mass of citric acid are dispersed in 100 parts by mass of ethanol to form an impregnation carbon source solution B1; the graphite core prepared above is added to the impregnation carbon source solution B1 and impregnated for 30 min at an impregnation pressure of 1.0 MPa; after impregnation, the material is centrifuged, dried, and then carbonized at 300 °C to obtain intermediate material C1. S6, 5 parts by mass of citric acid and 2 parts by mass of polymethyl methacrylate are dispersed in 100 parts by mass of ethanol to form an impregnation carbon source solution B2; the above intermediate material C1 is impregnated in the impregnation carbon source solution B2 for 8 minutes under a pressure of 0.1 MPa, and then centrifuged and dried to obtain intermediate material C2. S7, the above intermediate material C2 is placed in a box-type carbonization furnace under a protective atmosphere and heated to 750°C at a rate of 1.6°C / min, and then heated to 1000°C at a rate of 4°C / min and held for 4 hours to obtain the final graphite material with gradient pore carbon coating.

[0032] This embodiment 3 provides a three-dimensional graphite material with gradient porosity carbon-coated graphite, and a gradient porosity carbon-coated graphite anode material D. 50 =18.8μm, specific surface area is 1.5m² 2 / g, where the kernel is D 50 The artificial graphite has a thickness of 15.0 μm, with an outer layer of highly porous carbon with a porosity of 31.8% and an inner layer of dense amorphous carbon with a porosity of 8.5%. The carbon layer thickness is 110 nm.

[0033] The gradient porous carbon-coated graphite material obtained in Example 3 was tested for electrical performance. The initial discharge specific capacity was 353.6 mAh / g, the initial coulombic efficiency was 93.4%, the capacity retention rate was 96.3% after 600 cycles at 1C current, and the capacity retention rate was 90.3% at 5C / 0.5C.

[0034] Example 4: This embodiment 4 provides a method for preparing a porous carbon-coated graphite material with a gradient buffer layer, including: S1, 30 parts by mass of phenolic resin with a carbon residue of 60 are dispersed in 100 parts by mass of toluene solvent to form carbon source solution A; S2, 50 parts by weight of D 50 =6.0μm artificial graphite was added to 100 parts by mass of the above carbon source solution A and stirred for 4 hours to form a slurry; S3, the above slurry is added to a spray dryer and dried to obtain intermediate powder at a drying temperature of 250°C; S4. The intermediate powder is placed in a box-type carbonization furnace and heated to 750℃ under nitrogen protection and held for 1 hour to obtain a graphite core with carbon skeleton coated graphite powder. S5, 15 parts by mass of polyacrylonitrile are dispersed in 100 parts by mass of dimethylamide to form an impregnation carbon source solution B1; the graphite core prepared above is added to the impregnation carbon source solution B1 and impregnated for 60 min at an impregnation pressure of 0.2 MPa; after impregnation, the graphite core is centrifuged, dried, and then carbonized at 400 °C to obtain intermediate material C1. S6, 10 parts by mass of sucrose and 2 parts by mass of polystyrene are dispersed in 100 parts by mass of water to form an impregnation carbon source solution B2; the above intermediate material C1 is impregnated in the impregnation carbon source solution B2 for 8 minutes under a pressure of 0.2 MPa, and then centrifuged and dried to obtain intermediate material C2; S7, the above intermediate material C2 is placed in a box-type carbonization furnace under a protective atmosphere and heated to 900°C at a rate of 1.5°C / min, and then heated to 1200°C at a rate of 5°C / min and held for 1 hour to obtain the final graphite material with gradient pore carbon coating.

[0035] The graphite anode material with gradient porosity carbon-coated graphite provided in Example 4, wherein the gradient porosity carbon-coated graphite material D 50 =7.2μm, specific surface area is 1.8m² 2 / g, where the kernel is D 50 Artificial graphite with a thickness of 6.0 μm has an outer layer of highly porous carbon with a porosity of 30.2% and an inner layer of dense amorphous carbon with a porosity of 7.5%, and a carbon layer thickness of 120 nm.

[0036] The gradient porous carbon-coated graphite material obtained in Example 4 was tested for electrical performance. The initial discharge specific capacity was 351.4 mAh / g, the initial coulombic efficiency was 93.8%, the capacity retention rate was 96.7% after 600 cycles at 1C current, and the capacity retention rate was 92% at 5C / 0.5C.

[0037] Example 5: The method for preparing porous carbon-coated graphite material with a gradient buffer layer provided in Example 5 includes: S1, 25 parts by mass of epoxy resin with a carbon residue of 50 are dispersed in 100 parts by mass of acetone solvent to form carbon source solution A; S2, 50 parts by weight of D 50 =10.0μm artificial graphite was added to 100 parts by mass of the above carbon source solution A and stirred for 2.5h to form a slurry; S3, the above slurry is added to a spray dryer and dried to obtain intermediate powder at a drying temperature of 150°C. S4. The intermediate powder is placed in a box-type carbonization furnace and heated to 900℃ under nitrogen protection and held for 2 hours to obtain a graphite core with carbon skeleton coated graphite powder. S5, 15 parts by mass of sucrose are dispersed in 100 parts by mass of water to form an impregnation carbon source solution B1; the graphite core prepared above is added to the impregnation carbon source solution B1 and impregnated for 40 min at an impregnation pressure of 0.8 MPa; after impregnation, the graphite core is centrifuged, dried, and then carbonized at 300 °C to obtain intermediate material C1. S6, 8 parts by mass of sucrose and 3 parts by mass of polymethyl methacrylate are dispersed in 100 parts by mass of water to form an impregnation carbon source solution B2; the above intermediate material C1 is impregnated in the impregnation carbon source solution B2 for 5 min under a pressure of 0.2 MPa, and then centrifuged and dried to obtain intermediate material C2; S7, the above intermediate material C2 is placed in a box-type carbonization furnace under a protective atmosphere and heated to 700°C at a rate of 1.0°C / min, and then heated to 1000°C at a rate of 3°C / min and held for 2 hours to obtain the final graphite material with gradient pore carbon coating.

[0038] The gradient porous carbon-coated graphite material provided in Example 5 is a gradient porous carbon-coated graphite anode material D.50 =11.5μm, specific surface area is 2.0m² 2 / g, where the kernel is D 50 The artificial graphite has a thickness of 10 μm, with an outer layer of highly porous carbon with a porosity of 32.5%, an inner layer of dense amorphous carbon with a porosity of 8.7%, and a carbon layer thickness of 85 nm.

[0039] The gradient porous carbon-coated graphite material obtained in Example 5 was tested for electrical performance. The initial discharge specific capacity was 352.6 mAh / g, the initial coulombic efficiency was 93.6%, the capacity retention rate was 96.1% after 600 cycles at 1C current, and the capacity retention rate was 91.5% at 5C / 0.5C.

[0040] Example 6: The method for preparing porous carbon-coated graphite material with a gradient buffer layer provided in Example 6 includes: S1, 25 parts by mass of phenolic resin with a carbon residue of 70 are dispersed in 100 parts by mass of acetone solvent to form carbon source solution A; S2, 30 parts by weight of D 50 =8.0μm artificial graphite was added to 100 parts by mass of the above carbon source solution A and stirred for 2 hours to form a slurry; S3, the above slurry is added to a spray dryer and dried to obtain intermediate powder at a drying temperature of 150°C. S4. The intermediate powder is placed in a box-type carbonization furnace and heated to 800℃ under nitrogen protection and held for 1.5h to obtain a graphite core with carbon skeleton coated graphite powder. S5, 10 parts by mass of citric acid are dispersed in 100 parts by mass of water to form an impregnation carbon source solution B1; the graphite core prepared above is added to the impregnation carbon source solution B1 and impregnated for 35 minutes at an impregnation pressure of 1.0 MPa; after impregnation, the material is centrifuged, dried, and then carbonized at 350°C to obtain intermediate material C1. S6, 8 parts by mass of sucrose and 5 parts by mass of polymethyl methacrylate are dispersed in 100 parts by mass of water to form an impregnation carbon source solution B2; the above intermediate material C1 is impregnated in the impregnation carbon source solution B2 for 10 min under a pressure of 0.1 MPa, and then centrifuged and dried to obtain intermediate material C2. S7, the above intermediate material C2 is placed in a box-type carbonization furnace under a protective atmosphere and heated to 800°C at a rate of 1.6°C / min, and then heated to 1200°C at a rate of 4°C / min and held for 2 hours to obtain the final gradient porous carbon-coated graphite material.

[0041] The gradient porous carbon-coated graphite material provided in Example 6 is a gradient porous carbon-coated graphite anode material D. 50 =11.6m, specific surface area is 1.4m²2 / g, where the kernel is D 50 Artificial graphite with a thickness of 8.0 μm has an outer layer of highly porous carbon with a porosity of 31.3% and an inner layer of dense amorphous carbon with a porosity of 7.7%, and a carbon layer thickness of 200 nm.

[0042] The gradient porous carbon-coated graphite material obtained in Example 6 was tested for electrical performance. The initial discharge specific capacity was 352.2 mAh / g, the initial coulombic efficiency was 94.2%, the capacity retention rate after 600 cycles at 1C current was 96.8%, and the capacity retention rate at 5C / 0.5C was 91.2%.

[0043] Example 7: The method for preparing porous carbon-coated graphite material with a gradient buffer layer provided in Example 7 includes: S1, 15 parts by mass of petroleum asphalt with a carbon residue of 65 are dispersed in 100 parts by mass of toluene solvent to form carbon source solution A; S2, 40 parts by weight of D 50 =11.0μm artificial graphite was added to 100 parts by mass of the above carbon source solution A and stirred for 2.5h to form a slurry; S3, the above slurry is added to a spray dryer and dried to obtain intermediate powder at a drying temperature of 250°C; S4. The intermediate powder is placed in a box-type carbonization furnace and heated to 700℃ under nitrogen protection and held for 2 hours to obtain a graphite core with carbon skeleton coated graphite powder. S5, 15 parts by mass of polyacrylonitrile are dispersed in 100 parts by mass of N-methylpyrrolidone to form an impregnation carbon source solution B1; the graphite core prepared above is added to the impregnation carbon source solution B1 and impregnated for 50 min at an impregnation pressure of 0.5 MPa; after impregnation, the graphite core is centrifuged, dried, and then carbonized at 450 °C to obtain intermediate material C1. S6, 5 parts by mass of citric acid and 5 parts by mass of polyvinyl alcohol are dispersed in 100 parts by mass of water to form an impregnation carbon source solution B2; the above intermediate material C1 is impregnated in the impregnation carbon source solution B2 for 10 min under a pressure of 0.2 MPa, and then centrifuged and dried to obtain intermediate material C2. S7, the above intermediate material C2 is placed in a box-type carbonization furnace under a protective atmosphere and heated to 600°C at a rate of 1.5°C / min, and then heated to 1100°C at a rate of 4°C / min and held for 3 hours to obtain the final graphite material with gradient pore carbon coating.

[0044] The gradient porous carbon-coated graphite material provided in Example 7 is a gradient porous carbon-coated graphite anode material D. 50 =12.7μm, specific surface area is 2.5m² 2 / g, where the kernel is D50 The artificial graphite has a thickness of 11.0 μm, with an outer layer of highly porous carbon with a porosity of 33.6% and an inner layer of dense amorphous carbon with a porosity of 9.3%. The carbon layer thickness is 85 nm.

[0045] The gradient porous carbon-coated graphite material obtained in Example 7 was tested for electrical performance. The initial discharge specific capacity was 352.8 mAh / g, the initial coulombic efficiency was 93.1%, the capacity retention rate was 95.5% after 600 cycles at 1C current, and the capacity retention rate was 91.8% at 5C / 0.5C.

[0046] Example 8: The method for preparing porous carbon-coated graphite material with a gradient buffer layer provided in Example 8 includes: S1, 20 parts by mass of epoxy resin with a carbon residue of 60 are dispersed in 100 parts by mass of ethyl acetate solvent to form carbon source solution A; S2, 50 parts by weight of D 50 =15.0μm artificial graphite was added to 100 parts by mass of the above carbon source solution A and stirred for 3 hours to form a slurry; S3, the above slurry is added to a spray dryer and dried to obtain intermediate powder at a drying temperature of 180℃; S4. The intermediate powder is placed in a box-type carbonization furnace and heated to 850℃ under nitrogen protection and held for 2 hours to obtain a graphite core with carbon skeleton coated graphite powder. S5, 20 parts by mass of sucrose are dispersed in 100 parts by mass of ethanol to form an impregnation carbon source solution B1; the graphite core prepared above is added to the impregnation carbon source solution B1 and impregnated for 40 min at an impregnation pressure of 0.8 MPa; after impregnation, the material is centrifuged, dried, and then carbonized at 250 °C to obtain intermediate material C1. S6, 5 parts by mass of sucrose and 3 parts by mass of polystyrene are dispersed in 100 parts by mass of water to form an impregnation carbon source solution B2; the above intermediate material C1 is impregnated in the impregnation carbon source solution B2 for 5 minutes under a pressure of 0.1 MPa, and then centrifuged and dried to obtain intermediate material C2; S7, the above intermediate material C2 is placed in a box-type carbonization furnace under a protective atmosphere and heated to 650°C at a rate of 1.8°C / min, and then heated to 1200°C at a rate of 3°C / min and held for 2 hours to obtain the final graphite material with gradient pore carbon coating.

[0047] The graphite anode material with gradient porosity carbon coating provided in Example 8, namely, the graphite anode material with gradient porosity carbon coating D 50 =17.6μm, specific surface area is 2.4m² 2 / g, where the kernel is D 50The artificial graphite has a thickness of 15.0 μm, with an outer layer of highly porous carbon with a porosity of 33.4% and an inner layer of dense amorphous carbon with a porosity of 9.0%. The carbon layer thickness is 82 nm.

[0048] The gradient porous carbon-coated graphite material obtained in Example 8 was tested for electrical performance. The initial discharge specific capacity was 353.4 mAh / g, the initial coulombic efficiency was 92.7%, the capacity retention rate was 95.4% after 600 cycles at 1C current, and the capacity retention rate was 90.8% at 5C / 0.5C.

[0049] Comparative Example 1: The artificial graphite material of Comparative Example 1 was obtained according to S1-S4 of Example 1 above. The electrical performance test results of the obtained graphite material are as follows: initial discharge specific capacity 350.8 mAh / g, initial coulombic efficiency 94.8%, capacity retention rate of 92.3% after 600 cycles at 1C current, and capacity retention rate of 85.6% at 5C / 0.5C.

[0050] Comparative Example 2: The implementation conditions for Comparative Example 2 were the same as those for Example 1, except that lignin with a residual char rate of 35% was used as the carbon skeleton precursor. The electrical performance test results of the obtained graphite material were as follows: initial discharge specific capacity of 350.2 mAh / g, initial coulombic efficiency of 91.2%, capacity retention rate of 90.2% after 600 cycles at 1C current, and capacity retention rate of 88.5% at 5C / 0.5C.

[0051] Comparative Example 3: The implementation conditions of Comparative Example 3 were the same as those of Example 1, except that step (6) was not performed, i.e., the impregnation was only performed once. The electrical performance test results of the obtained graphite material were as follows: initial discharge specific capacity 351.24 mAh / g, initial coulombic efficiency 94.2%, capacity retention rate after 600 cycles at 1C current 93.6%, and capacity retention rate at 5C / 0.5C 86.8%.

[0052] The performance test results of Examples 1-8 and Comparative Examples 1-3 are described below: D 50 Particle size test: The graphite materials prepared in Examples 1-8 and Comparative Examples 1-3 were dispersed in dispersants and added to a laser particle size analyzer for testing.

[0053] Specific surface area test: The graphite materials prepared in Examples 1-8 and Comparative Examples 1-3 were tested using a BSD-BET400 fully automatic rapid specific surface area analyzer with direct comparison method.

[0054] Capacity testing: The graphite anode materials prepared in Examples 1-8 and Comparative Examples 1-3 were mixed with conductive agent and PVDF in a weight ratio of 93:3:4 to form a slurry, which was then coated on copper foil to prepare anode sheets. After drying, the anode sheets were used as anodes and lithium sheets were used as positive electrodes to assemble lithium-ion batteries. Performance testing was conducted using the following methods: The anode materials were tested for electrical performance using a LANHE multi-channel battery testing system, etc. The charge-discharge voltage was 0.01-2.0V and the charge-discharge rate was 0.1C. The initial discharge specific capacity and initial coulombic efficiency were obtained.

[0055] Cyclic testing: The graphite anode materials prepared in Examples 1-8 and Comparative Examples 1-3 were used to make anodes, lithium cobalt oxide as cathode, and 1M-LiPF6+EC:DEC:DMC (volume ratio 1:1:1) solution as electrolyte to assemble full cells. The cells were charged to 4.2V at a 1C rate and then discharged to 2.6V at a 1C rate. The capacity retention rate was tested after 600 cycles.

[0056] Rate performance test: After assembling full cells with the graphite anode materials prepared in Examples 1-8 and Comparative Examples 1-3, the cells were charged to 4.2V at a rate of 0.5C, and then discharged to 2.6V at 0.5C and 5C, respectively. The capacity retention rate at 5C / 0.5C was tested as the discharge capacity at 5C (mAh / g) / the discharge capacity at 0.5C (mAh / g).

[0057] The performance test results of Examples 1-8 and Comparative Examples 1-3 are shown in Table 1 below: Table 1 Performance test results of Examples 1-8 and Comparative Examples 1-3 The experimental results above show that the graphite material with gradient pore distribution prepared according to the controlled conditions described in this invention possesses excellent electrochemical performance, with a specific surface area of ​​3 m². 2 Below / g, the cycle and rate performance of the anode material have been effectively improved.

[0058] The graphite anode material obtained in Comparative Example 1 has inferior cycle performance and rate performance compared to Example 1 because its coating layer is a uniform and dense carbon layer, Li + The relatively high diffusion activation energy limits its rate performance; the coating layer has limited buffering capacity against volume expansion during graphite charging and discharging, and after repeated charging and discharging, it is prone to carbon layer cracking, increased side reactions, and decreased cycle performance.

[0059] Comparative Example 2 used lignin with low carbon residue as a carbon skeleton precursor. The resulting carbon skeleton had excessive porosity, resulting in low penetration resistance of the impregnation solution during impregnation. This led to a uniform distribution and the failure to form the expected gradient pores. Consequently, the resulting graphite anode material had a large specific surface area, low initial efficiency, and relatively poor cycle and rate performance.

[0060] Comparative Example 3 did not employ stepwise impregnation, resulting in a graphite anode material with a coating layer where the pore size of the inner and outer layers differed, but not significantly. The insufficient porosity of the outer layer limited the Li... + The diffusion rate and electrolyte wetting affect the rate capability and cycle performance.

[0061] The above-described embodiments are only used to illustrate the technical solutions of the present invention, and are not intended to limit it. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some of the technical features. Such modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention, and should all be included within the protection scope of the present invention.

Claims

1. A graphite material with gradient porosity carbon-coated graphite, characterized in that, It includes a graphite core and a first carbonized graphite coating layer and a second carbonized graphite coating layer sequentially covering the outside of the graphite core; wherein, the carbon pore size of the first carbonized graphite coating layer is smaller than that of the second carbonized graphite coating layer, the porosity of the first carbonized graphite coating layer is 8%~12%, and the porosity of the second carbonized graphite coating layer is 25~40%.

2. The graphite material with gradient porosity carbon-coated graphite according to claim 1, characterized in that, The graphite core includes graphite powder and a carbon skeleton layer formed by high-temperature carbonization covering the graphite powder, wherein the carbon skeleton is artificial graphite.

3. The graphite material with gradient porosity carbon-coated graphite according to claim 2, characterized in that, The thickness of the carbon skeleton layer is 50-200 nm; the total thickness of the first carbonized graphite coating layer and the second carbonized graphite coating layer is 50-200 nm.

4. A method for preparing a carbon-coated graphite material with gradient porosity, characterized in that, Including the following steps: S1, Disperse organic carbon sources with a residual carbon value ≥50% in a solvent to form carbon source solution A; S2, dispersing graphite powder in carbon source solution A to form a slurry; S3, the above slurry is spray-dried to remove the solvent and obtain intermediate powder; S4, the intermediate powder is carbonized at a high temperature of 800-1200℃ to obtain a graphite core with a carbon skeleton layer coating graphite powder. S5, the graphite core is immersed in carbon source solution B1 for T1 time, centrifuged and dried, and then subjected to low-temperature carbonization at 200-500℃ to obtain intermediate material C1; S6, the intermediate material C1 is immersed in a carbon source solution B2 containing additives for time T2, centrifuged and dried to obtain intermediate material C2; wherein, the carbon source concentration in the carbon source solution B1 is greater than the carbon source concentration in the carbon source solution B2, the time T1 is greater than the time T2, and the additive is one or more selected from polyvinyl alcohol, polystyrene, polymethyl methacrylate, and polyvinyl alcohol. S7, intermediate material C2 is carbonized at high temperature of 1000-1400℃ to obtain carbon-coated graphite material with gradient pores.

5. The method for preparing carbon-coated graphite material with gradient pores according to claim 4, characterized in that, The organic carbon source of the carbon source solution A is selected from one or more of petroleum asphalt, coal tar pitch, epoxy resin, and phenolic resin; the solvent is selected from one or more of toluene, ethyl acetate, acetone, ethanol, and tetrahydrofuran; the graphite powder is artificial graphite, D. 50 It is 5-20μm.

6. The method for preparing carbon-coated graphite material with gradient pores according to claim 4, characterized in that, The carbon source of carbon source solution B1 is selected from one or more of sucrose, polyacrylonitrile, and citric acid, and the solvent is selected from one or more of water, ethanol, N-methylpyrrolidone, and dimethylamide; the carbon source of carbon source solution B2 is selected from one or more of sucrose, polyacrylonitrile, and citric acid, and the solvent is selected from one or more of water and ethanol.

7. The method for preparing carbon-coated graphite material with gradient pores according to claim 6, characterized in that, The carbon source concentration in carbon source solution B1 is 10-25 wt%, the carbon source concentration in carbon source solution B2 is 5-15 wt%, and the concentration of additives is 1-5 wt%; the time T1 is 30-120 min, and the time T2 is 5-60 min.

8. The method for preparing carbon-coated graphite material with gradient pores according to claim 4, characterized in that, In step S7, the intermediate material C2 is heated to 600-900℃ at a heating rate of 1-3℃ / min under a protective atmosphere, and then heated to 1000-1400℃ at a high temperature at a heating rate of 2-5℃ / min, which is higher than the aforementioned low temperature range, to obtain a carbon-coated graphite material with gradient pores.

9. A graphite material with gradient porosity carbon-coated graphite, characterized in that, Prepared using the preparation method described in any one of claims 4-8.

10. The application of a gradient-pore carbon-coated graphite material according to any one of claims 1-9 in a battery anode material.

Citation Information

Cited By

  • Porous-structure graphite negative electrode material and preparation method thereof

    CN122325228A